Al-Uzmah al-Biṭrikiyah fī Riwāyati “Nisyān” Li Ahlām Mustagānemiy (Dirāsah Nisāiyah ‘alā Ḍaui Naẓariyah Julia Kresteva) - Husna wati Zahra; Arief Rahman Hakim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
This research aims to find out the forms of the patriarchal crisis and the factors that lead to the emergence of the patriarchal problem represented in the novel